The Integration of Classic Cars as an Alternative Investment in Wealth Management Environments and the Possible Influence of Behavioral Finance - Hoffmann, Sebastian (European Journal of Multidisciplinary Studies, 2018)
Investing in classic cars can be a supplement to traditional investments for private clients in wealth management. However, the special features of this exotic asset class have to be taken into account. In the case of an investment, risk factors such as ongoing costs, market transparency and liquidity have to be considered. In contrast, opportunities arise from potential portfolio optimization as well as of the realization of an “emotional return”. General return forecasts can only be made to a limited extent. Rather, it requires an individual yield calculation, taking the circumstances and intentions of the investor into account. The Classic Car Banking Concept, which is presented in this paper, demonstrates the ability to integrate the investment in classic cars into an existing wealth management structure. Thereby, the further diversification of an investor’s portfolio by adding classic cars offers an interesting earning potential in the current situation of historically low interest rates in many parts of the world. Moreover, Classic Car Banking as a segment of wealth management in general has the potential to use the conceivable emotional involvement of investors in order to intensify the relationship between clients and consultants. Nevertheless, selected concepts of behavioral finance are able to explain the downside of potentially emotional investments. Concepts such as Anchoring, the Endowment Effect, Mental Accounting and Overconfidence are related to insufficient decision making which, in the case of investments, leads to inadequate monetary returns.